JURIDICAL IMPLICATIONS THE JOINT MEETING OF THE PURA DWIJAWARSA FOUNDATION IS BASED ON LEGAL CERTAINTY - Melati Putri Nusa, Luh Putu Ayu Meilina; Djumikasih; Dyah Widhiawati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The Foundation Law provides an understanding that a foundation is a legal entity engaged in religious, social, and humanitarian fields. This research discusses the juridical implications of the joint meeting held at Yayasan Pura Dwijawarsa with the aim of appointing the foundation's trustees, the regulation of the joint meeting is contained in article 7 number 6 of the Articles of Association contained in the Deed of Establishment of Yayasan Pura Dwijawarsa Number 29 dated April 25, 2008 made before notary Niluh Elita Mahariany S.H., M.Kn, the article states that if for any reason the foundation does not have a trustee, then since the vacancy is obliged to appoint a trustee based on the decision of a joint meeting by the management and supervisory organs. But what happened in Yayasan Pura Dwijawarsa, the joint meeting aimed at appointing the coach was carried out by the management and supervisors who had ended their term of office. This research is a socio-legal research using a sociological juridical approach. The results of the analysis show that there are several impacts arising from the existence of the joint meeting so that it is not in accordance with one of the objectives of the law, namely legal certainty.